The impact of the COVID-19 pandemic on the mental health of refugees - Manzoni, Dino (Dve domovini, 2024)
As part of a systematic literature search, the authors independently reviewed 256 articles and included 12 papers in the final selection. The synthesis of the results showed that the psychological distress of refugees increased significantly following the outbreak of the COVID-19 pandemic. The main mental health difficulties of refugees addressed in the analyzed studies were stress, anxiety, depression, and post-traumatic stress disorder. The mental health of refugees during the pandemic appeared to be closely related to their poor living conditions and socioeconomic situation, social exclusion, unemployment, inadequate housing, lack of access to health and social services, discrimination, and lack of essential goods.
Keywords: begunci; COVID-19; duševno zdravje; pandemije; pregled literature; stres